Ameliorasi Media Tailing Pascatambang Timah dengan Sabut Kelapa pada Budidaya Pakcoy (Brassica rapa L. chinensis) dengan Sistem Irigasi Growick: Ameliorasi Media Tailing Pascatambang Timah dengan Sabut Kelapa pada Budidaya Pakcoy (Brassica rapa L. chinensis) dengan Sistem Irigasi Growick - Ismed Inonu; Rion Apriyadi; Dera Utari (Universitas Bangka Belitung, 2021)
Post-tin mining is mostly in the form of sand tailings, with a texture dominated by the sand fraction, so that the water holding capacity is low. The growick irrigation system was developed for plant cultivation in post-mining land, by utilizing a capillary axis to maintain the water content of the planting medium, it is necessary to ameliorate it with coconut husk. This study aims to determine the effect of the dose of coconut husk added to the sand tailings medium on the growth and yield of pakcoy with growick tailings irrigation system. Research held in the experiment and research Station of Universitas Bangka Belitung, Balunijuk Village, Merawang District, Bangka Regency from January to April 2020. The study used a single completely randomized design (CRD) with 3 replications. The treatment dosage of coconut husk studied was 0; 200; 400; 600; 800, and 1000g per polybag. The data obtained will be analyzed statistically using the Analysis of Variance and Duncan's Multiple Range Test (DMRT) α = 5%. The results showed that the growth and production of pakcoy were affected by the dose of coconut husk ameliorant, and the best growth and production was obtained at a dose of 600 g. Efficient use of water by plants at a dose of 600 g is the most efficient.